2023
DOI: 10.3389/fbrio.2023.1253097
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cell envelope ultrastructure and the antibacterial properties of a novel hydrophobic eumelanin-inspired derivative

Daniel R. Reed,
Katherine Nehmzow,
Martha A. Essandoh
et al.

Abstract: IntroductionUnique impermeability properties of the gram-negative outer cell envelope typically render these organisms intrinsically resistant to hydrophobic antibacterial compounds. Eumelanin-inspired indoylenephenyleneethynylene (EIPE) compounds possess scaffolding to which functional groups were attached to potentially provide antibacterial properties in the forms of hydrophilic (EIPE-HCl) and hydrophobic (EIPE-1) derivatives.MethodsStandardized disk agar diffusion and microbroth dilution bioassays were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…While its original purpose was as a building block for organic semiconductors, it was later discovered that this core has the interesting capability of serving as a foundation for the integration of antibactericidal moieties and possesses intrinsic antimicrobial activity that causes cytoplasmic membrane disruption in gram positive bacteria. Additionally, it was revealed that thirteen different strains from eight gram-positive bacteria, including two methicillin resistant strains were found to be susceptible to EIPE-1 ( Adhikari et al, 2022 ; Reed et al, 2023 ). While not previously studied in fungal organisms, we found enough evidence to support studying this compound as an antifungal against Cryptococcus isolates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While its original purpose was as a building block for organic semiconductors, it was later discovered that this core has the interesting capability of serving as a foundation for the integration of antibactericidal moieties and possesses intrinsic antimicrobial activity that causes cytoplasmic membrane disruption in gram positive bacteria. Additionally, it was revealed that thirteen different strains from eight gram-positive bacteria, including two methicillin resistant strains were found to be susceptible to EIPE-1 ( Adhikari et al, 2022 ; Reed et al, 2023 ). While not previously studied in fungal organisms, we found enough evidence to support studying this compound as an antifungal against Cryptococcus isolates.…”
Section: Discussionmentioning
confidence: 99%
“…This membrane maintains the viability of a cell and prevents the free exchange of molecules from the cytoplasm to the cell’s environment and vice versa ( Upadhya et al, 2023 ). Previously, microorganism membrane permeability to hydrophobic molecules was identified as being pertinent for susceptibility to the molecule ( Reed et al, 2023 ). Since C. neoformans has a high cellular surface hydrophobicity due to the presence of mannoproteins, lipids, glucan, and chitin molecules, it could allow the hydrophobic EIPE-1 molecule to passively diffuse across the membrane into the cell ( van der Rest et al, 1995 ; Danchik and Casadevall, 2020 ; Vij et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations